Pregabalin-induced first degree atrioventricular block in a young patient treated for pain from extrapulmonary tuberculosis - Schiavo, Alessandra; Stagnaro, Francesca M.; Salzano, Andrea; Marra, Alberto M.; Bobbio, Emanuele; Valente, Pietro; Grassi, Simona; Miniero, Martina; Arcopinto, Michele; Matarazzo, Margherita; et al. (Monaldi Archives for Chest Disease, 2017)
Pregabalin, widely used in the treatment of several pain disorders, is usually well tolerated. Uncommonly, the drug may induce cardiac side effects, rarely prolongation of the PR interval. The latter has never been described in patients with healthy heart or normal renal function. We characterize a unique case of a young man with extrapulmonary tuberculosis and no detectable or known cardiac or kidney diseases, treated with pregabalin to control the severe pain due to the involvement of the spinal cord by the tuberculosis, showing an atrioventricular (AV) block due to pregabalin administration. The reported case emphasizes the need of monitoring PR interval during treatment with pregabalin, even in patients without background of cardiac or renal diseases.Â